Epidemiological status and associated factors of frailty and pre-frailty in older adults with asthma in China: A national cross-sectional study - Zeng, Xue-zhai; Meng, Ling-bing; Jia, Na; Shi, Jing; Zhang, Chi; Li, Ying-ying; Hu, Xing; Hu, Jia-bin; Li, Jian-yi; Wu, Di-shan; Li, Hui; Qi, Xin; et al. (Frontiers in Public Health, 2023)
Objective: There are few studies on the prevalence and factors associated with frailty and pre-frailty in elderly asthmatic patients worldwide. The aim of this study was to examine the epidemiological status and factors associated with frailty and pre-frailty in elderly asthmatic patients in China. Research design and methods: Data were obtained from the Sample Survey of Aged Population in Urban and Rural China in 2015, a nationwide cross-sectional survey covering 224142 elderly people aged 60 years or older in 31 provinces/autonomous regions/municipalities in mainland China. We performed frailty and pre-frailty assessments using the frailty index, and the diagnosis of asthma in the elderly was self-reported based on the history of the physician's diagnosis. Results: 9,416 elderly patients with asthma were included in the study. The age-sex standardized prevalence of frailty and pre-frailty in Chinese elderly with asthma was 35.8% (95% CI 34.8%-36.7%) and 54.5% (95% CI 53.5%-55.5%). Multinomial logistic regression analysis showed that increased age, female, illiteracy, living alone, poor economic status, ADL disability, comorbid chronic diseases, previous hospitalization in the past year, and residence in northern China were associated with frailty and pre-frailty in elderly asthmatics. Conclusion: The prevalence of frailty and pre-frailty in elderly Chinese asthmatics is very high, and assessment of frailty should become routine in the management of elderly asthmatics. Appropriate public health prevention strategies based on identified risk factors for frailty in elderly asthmatics should be developed to reduce the burden of frailty in elderly Chinese asthmatics.